Pemberdayaan Masyarakat melalui Program Urban Farming Terintegrasi Buruan SAE di Kota Bandung - Haqi, Muamar; Armansyah, Armansyah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Haqi, M., Armansyah, A. (2023). Community empowerment through the integrated urban farming program buruan SAE in Bandung City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 513-522). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Bandung as a metropolitan city and service city is experiencing land conversion. The food situation in Bandung City is that almost 96% of the food in Bandung City is imported from outside the Bandung City area, making it vulnerable to food insecurity regarding food availability and sufficiency. The Bandung City Government established an integrated urban farming program called Buruan SAE. This program takes the form of community empowerment activities which aim to overcome food inequality through the use of yards or empty land to make people more independent in meeting their own food needs. This research aimed to describe a form of community empowerment through an integrated urban farming program in the Buruan SAE Pemuda Mandiri group, Sukawarna Subdistrict, Bandung City. Apart from that, this research is an effort to improve urban farming that is suitable for the city of Bandung in the future. The method uses qualitative with a descriptive approach. Data collection techniques used were interviews, observation, documentation, and literature studies. Interviews were conducted in March 2023 with active administrators of Buruan SAE Pemuda Mandiri and supporting informants. The research results show that the stages of community empowerment through the urban farming program in the Pemuda Tangguh farmer group go through three stages, namely the awareness, capacity building, and empowerment stages. Urban farming has a sustainable impact on the economic aspect by meeting their own food needs and gaining profits from the harvest. In the socio-cultural aspect, creating a culture of cooperation and helping each other in food security and the ecological aspect, creating green open spaces in urban areas. Based on the research that has been conducted, it can be concluded that the Buruan SAE Pemuda Mandiri urban farming program shows that community empowerment is being realized well.